Base-Free Palladium-Catalyzed Cross-Coupling of Arylsulfonium Salts with Sodium Tetraarylborates - Vasu, Dhananjayan; Yorimitsu, Hideki; Osuka, Atsuhiro (Synthesis, 2015)
Palladium-catalyzed cross-coupling reactions of arylsulfonium salts with sodium tetraarylborates were found to proceed smoothly without recourse to an additional base, providing a new, reliable route to biaryls from organosulfur compounds.
Keywords: C–S cleavage; C–C bond formation; cross-coupling; sulfonium salts; sodium tetraarylborates; palladium